SEJARAH PENDIDIKAN PESANTREN BANJARSARI DALAM KERANGKA HISTORIOGRAFI INDONESIASENTRISME - Akhlis Syamsal Qomar (JUSAN: Jurnal Sejarah Peradaban Islam Indonesia, 2024)
Abstract: Banjarsari Islamic boarding school village is one of the fief villages at the same time became the most influential religious educational institution in Java in the 18-19 centuries. YearThat year was the golden age of the well-known Banjarsari Islamic boarding school village as a village that is politically and economically independent from the practice of the economic exploitation system colonialism which was very impartial to the indigenous people of that time. As a fief village, Banjarsari is free from the influence and interference of any party, not except the government Dutch colonial. Although in the field of Dutch politics several times tried to interfere the internal affairs of the Banjarsari fief until it managed to split it into two, namely the village the fief of Banjarsari Kulon and the village of the fief of Banjarsari Wetan around 1815-16. as strong whatever the Dutch wish to interfere in Banjarsari's internal affairs, but he did not manage to enter in the field of economics until 1870. The internal dynamics of the Banjarsari fief economy walk independently. Based on the traditional rural economic system which focuses on the agricultural sector. In Banjarsari, in particular, the second sector is developing namely the trade of palm fiber brooms as a local product that helps boost the economy the community so that it makes Banjarsari a truly independent fief village. Keyword: Banjarsari Islamic Boarding School, agricultural sector, trade sector; independent village.